PENGARUH DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN KANTOR PERDAGANGAN DAN KOPERASI KABUPATEN SUBANG - Juheti, Ai; Sulaeman, Eman (Pandawan, 2021)
This research aims to determine the correlation and influence of work discipline and compensation on the performance of employees of subang district trade and industrial cooperative office. The research data was taken from a sample of 98 employees. Hypothesis testing using t test and F test. This research data analysis technique uses product-moment correlation analysis method and path analysis method with the help of SPSS v.25, which shows that work discipline and compensation have a correlation of 31.3%. Then partially the work discipline had a significant effect of 23.4% and compensation had a significant effect of 14.6% on employee performance. Furthermore, simultaneous work discipline and compensation had a significant effect of 38% on employee performance. The remaining 62% is the contribution of other variables (£) that were not studied in this study.